Peningkatan Pemahaman Konsep Hubungan Antar Garis Menggunakan Model Discovery Learning Di Kelas IV SD - Yanti, Febri; Fachruddin, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe the results of the Improvement of the Ability of Understanding the Concept of Inter-Class Relationship Using the Discovery Learning Model in Grade IV of Elementary School. This type of research is PTK using quantitative and quantitative. The research subjects were teachers and 25 students. The results showed that: (1) the average RPP ranking of the first cycle was 85.7% to 94.6% in the second cycle with an increase of 8.9%, (2) the results of the curriculum aspects of the first cycle 78.1% to 92, 2% in the second cycle with an increase of 14.1%, and the results of student competency assessment 78.1% to 92.2% in the second cycle with an increase of 14.1%, (3) the results of the ability to understand the concepts of students in cycle I 66 , 4 to 86.2 in the second cycle with an increase of 19.8%. Keywords: Discovery Learning, Concept Understanding Ability